Aqueous zinc ion battery electrolyte using wheat straw extract as biomass organic salt additive and application thereof

By using straw extract as biomass organic salt additive in aqueous zinc ion batteries, the problem of poor reversibility of zinc negative electrodes is solved, and the inhibition of zinc dendrites, the long cycle stability of the battery and high Coulomb efficiency are achieved.

CN114883670BActive Publication Date: 2025-03-18ANHUI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210473452.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-29
Publication Date
2025-03-18
Estimated Expiration
2042-04-29

AI Technical Summary

Technical Problem

The zinc negative electrode of aqueous zinc ion batteries has poor reversibility, resulting in dendrite generation, corrosion and hydrogen evolution side reactions, limiting its commercial application.

Method used

Straw extract is used as biomass organic salt additive to form zinc ion migration channels by adsorption on the surface of zinc sheets, guiding Zn2+ to uniformly deposition along the Zn(002) crystal plane to inhibit dendrites generation and corrosion.

Benefits of technology

The negative electrode zinc sheet reversibility of the aqueous zinc ion battery is significantly improved, the cycle stability and Coulomb efficiency of the battery are extended, and side reactions such as hydrogen evolution are inhibited.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114883670B_ABST
    Figure CN114883670B_ABST
Patent Text Reader

Abstract

The invention discloses an aqueous zinc ion battery electrolyte using waste straw extract as a biomass organic salt additive. The aqueous zinc ion battery electrolyte specifically comprises zinc sulfate, deionized water and a biomass organic salt additive; the biomass organic salt additive is sodium lignin sulfonate, calcium lignin sulfonate and ammonium lignin sulfonate. The Zn / Zn symmetrical battery with 0.05M biomass organic salt additive has a current density of 5mAcm ‑2 The full battery with sodium lignin sulfonate electrolyte additive (Zn / / MnO2, Zn / / PANI) showed higher stable cyclability and capacity retention rate. The lignin sulfonate in the present invention can form Zn 2+ Migration channel, guiding Zn 2+ It is deposited along the Zn (002) crystal plane, effectively protecting the negative electrode zinc sheet.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an aqueous zinc ion battery electrolyte using a wheat straw extract as a biomass organic salt additive and application thereof, belonging to the field of aqueous zinc ion battery electrolyte additives. Background Art

[0002] Aqueous zinc-ion batteries have a suitable potential (-0.76 V vs. SHE), high gravimetric / volume theoretical capacity (820 mAh g -1 / 5855mAh cm -2 ), environmentally friendly, resource-rich, highly safe, and non-flammable, it is a promising alternative to lithium-ion batteries in new battery storage systems. However, the poor reversibility of the zinc anode (dendrites, corrosion, and byproduct problems) severely limits the practical commercialization of AZIBs. The poor reversibility stems from: 1) At the electrolyte / electrode interface, the uneven local electric field distribution leads to uneven zinc plating and zinc dendrite growth, which inevitably leads to a shortened battery life after long-term cycling. 2) In the liquid phase, Zn 2+ Combines with water molecules to form Zn(H2O)6 2+ The strong solvation structure during the zinc plating process has a high desolvation barrier, which directly affects the formation of the Zn core. These water molecules belonging to the solvation layer are chemically reactive, so H2 precipitation is easily generated at the electrolyte / electrode interface, affecting the coulombic efficiency of the Zn plating / stripping process. 3) H2 release leads to local pH increase and accumulation of byproducts (such as Zn4SO4(OH)6·xH2O).

[0003] So far, a variety of methods have been developed to achieve high reversibility of zinc anode, such as anode design (e.g., construction of protective layer, main material structure design and adoption of zinc alloy), separator modification and electrolyte optimization. Among them, electrolyte optimization is a simple, economical and practical expedient. So far, the methods of electrolyte optimization include salt-in-water electrolyte (high concentration) and electrolyte additive (low concentration) strategies. The strategy of salt-in-water electrolyte is to suppress water-induced hydrogen evolution and side reactions by reducing the amount of active water. However, salt-in-water electrolyte will lead to a sharp drop in ionic conductivity and a surge in cost. In contrast, adding appropriate additives to the electrolyte is considered to be one of the efficient methods to inhibit dendrite growth. In recent years, reported additives include ionic additives (such as Ce 3+ EDTA 4- 、TMA + ) and organic additives (such as methanol, glucose, ether). Generally speaking, electrolyte additives guide uniform Zn 2+Nucleation or adjustment of the solvation structure of the Zn hydration layer to inhibit the hydrogen evolution reaction. Although these additives have achieved some success, the sources of these materials come from extremely limited and non-renewable fossil or ore energy, which greatly reduces the environmental friendliness and low-cost advantages of AZMB. Therefore, there is still an urgent need to develop new electrolyte additives that are renewable, non-toxic, naturally abundant, and easy to prepare for commercialization.

[0004] Sodium lignin sulfonate (SL), calcium lignin sulfonate (CL) and ammonium lignin sulfonate (AL) are organic salts of lignin sulfonic acid groups, a class of green plant extracts extracted from straw, a by-product of the papermaking industry, and can be obtained in large quantities at low cost. In addition, lignin sulfonate has satisfactory water solubility and bonding ability, and is a non-toxic and biodegradable renewable resource. However, only 10% of lignin sulfonate can be recycled as low-value products (dispersants, water reducers, intermediates in the dye industry), resulting in a waste of resources. Therefore, exploring novel and advanced applications of lignin sulfonates (such as electrolyte additives in the energy field) is obviously a fascinating idea. Summary of the invention

[0005] In view of the above problems of the prior art, the present invention provides an aqueous zinc ion battery electrolyte using wheat straw extract as a biomass organic salt additive and its application. The lignin sulfonic acid-based electrolyte additive forms a channel for zinc ion migration by adsorbing on the surface of the zinc sheet, guiding Zn 2+ The deposition is carried out along the Zn (002) crystal plane, aiming to improve the reversibility of the negative electrode zinc sheet of the aqueous zinc ion battery, prevent the formation of zinc dendrites during the charge and discharge process, and inhibit the corrosion of the zinc sheet by the aqueous electrolyte and side reactions such as hydrogen evolution.

[0006] The invention discloses an aqueous zinc ion battery electrolyte which uses wheat straw extract as a biomass organic salt additive and comprises zinc sulfate, deionized water and the biomass organic salt additive.

[0007] Furthermore, the biomass organic salt additive is sodium lignin sulfonate, calcium lignin sulfonate or ammonium lignin sulfonate.

[0008] The aqueous zinc ion battery electrolyte is prepared by the following steps:

[0009] Step 1: Weigh 3-5 g of zinc sulfate hexahydrate (ZnSO4·7H2O) and 0.1-0.5 g of biomass organic salt additive powder and dissolve them in deionized water, and prepare 3-7 ml of the mixed liquid by constant volume, and stir with a magnetic stirrer to accelerate the dissolution and uniform dispersion;

[0010] Step 2: The solution obtained in step 1 is filtered by suction through a microporous filter membrane to remove insoluble impurities, thereby obtaining an electrolyte having a biomass organic salt additive concentration of 0.01 to 0.1 M, wherein the concentration of ZnSO4 in the electrolyte is 1 M.

[0011] The invention discloses an application of an aqueous zinc ion battery electrolyte using wheat straw extract as a biomass organic salt additive, and constructs an aqueous zinc ion battery using the aqueous zinc ion battery electrolyte.

[0012] The aqueous zinc ion battery includes a Zn / Zn symmetrical battery, a Zn / Cu half-cell, a Zn / / MnO2, a Zn / / PANI full battery, etc.

[0013] Furthermore, the electrolyte is 50 μL.

[0014] The characterization process of the present invention comprises:

[0015] The Zn / Zn symmetric cells with 1M ZnSO4 electrolyte containing different concentrations (0, 0.01M, 0.05M, 0.1M) of sodium lignin sulfonate, calcium lignin sulfonate and ammonium lignin sulfonate additives were tested at different current densities of 1-10 mA cm -2 and area capacity of 1 to 10 mAh cm -2 The surface morphology of the Zn sheet, XRD and the number of cycles of the symmetric battery are shown below to prove that the sodium lignin sulfonate additive can guide the uniform deposition of zinc ions on the surface of the negative electrode zinc sheet.

[0016] The Zn / Cu half-cells with 1M ZnSO4 electrolyte containing different concentrations (0, 0.01M, 0.05M, 0.1M) of sodium lignin sulfonate, calcium lignin sulfonate and ammonium lignin sulfonate additives were assembled and tested at different current densities of 1-4 mA cm -2 and area capacity of 0.5 to 2 mAh cm -2 The surface morphology of the Cu sheet, XRD and Coulomb efficiency of the half-cell were compared to explore the effect of lignin sulfonate on the morphology of zinc ion deposition.

[0017] In the electrolytic cell, copper foil was used as the working electrode, zinc sheet was used as the counter electrode, sodium lignin sulfonate, calcium lignin sulfonate and ammonium lignin sulfonate were used as electrolyte additives and zinc sulfate was used to prepare the electrolyte, a zinc layer was plated on the copper sheet, and the mechanism of lignin sulfonate guiding the uniform deposition of zinc was obtained through XRD measurement.

[0018] Full cells with / without sodium lignin sulfonate additive electrolyte (Zn / / MnO2, Zn / / PANI) were assembled to determine the charge and discharge curves and long-cycle stability.

[0019] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0020] 1. The electrolyte additive used in the present invention is taken from discarded wheat straw. The raw material is green, environmentally friendly and inexpensive. It can effectively protect the negative zinc sheet of the zinc ion battery, prevent the formation of zinc dendrites during the charge and discharge process, and inhibit the corrosion of the aqueous electrolyte to the zinc sheet and side reactions such as hydrogen evolution.

[0021] 2. The Zn / Zn symmetrical battery with 0.05M sodium lignin sulfonate, calcium lignin sulfonate and ammonium lignin sulfonate additives in the present invention has a current density of 5 mA cm -2 and an area capacity of 0.5 mAh cm -2 The Zn / Cu half-cells with 0.05 M sodium lignin sulfonate, calcium lignin sulfonate, and ammonium lignin sulfonate additives exhibited excellent cycling stability at a current density of 0.5 mA cm -2 and an area capacity of 0.25 mAh cm -2 The full battery with sodium lignin sulfonate electrolyte additive (Zn / / MnO2, Zn / / PANI) showed higher stable cyclability and capacity retention than the full battery with pure zinc sulfate electrolyte.

[0022] 3. The lignin sulfonic acid electrolyte additive in the present invention can form a zinc ion migration channel by adsorbing on the surface of the zinc sheet, guiding Zn 2+ It is deposited along the Zn (002) crystal plane, thereby effectively protecting the negative electrode zinc sheet of the aqueous zinc ion battery, preventing the formation of zinc dendrites during the charge and discharge process, and inhibiting the corrosion of the aqueous electrolyte to the zinc sheet and side reactions such as hydrogen evolution. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The Zn / Zn symmetric battery assembled with different concentrations (0, 0.01M, 0.05M, 0.1M) of sodium lignin sulfonate obtained in Example 1 of the present invention was subjected to a current density of 5 mA cm -2 and an area capacity of 0.5 mAh cm -2 Next long loop picture;

[0024] Figure 2 The Zn / Zn symmetric battery assembled with different concentrations (0, 0.01M, 0.05M, 0.1M) of calcium lignin sulfonate obtained in Example 1 of the present invention was subjected to a current density of 5 mA cm -2 and an area capacity of 0.5 mAh cm -2 Next long loop picture;

[0025] Figure 3The Zn / Zn symmetric battery assembled with different concentrations (0, 0.01M, 0.05M, 0.1M) of ammonium lignin sulfonate obtained in Example 1 of the present invention was subjected to a current density of 5 mA cm -2 and an area capacity of 0.5 mAh cm -2 Next long loop picture;

[0026] Figure 4 XRD photo of the negative zinc sheet of the Zn / Zn symmetric battery assembled with sodium lignin sulfonate, calcium lignin sulfonate and ammonium lignin sulfonate of the same concentration (0.05M) obtained in Example 1 of the present invention after 50 cycles;

[0027] Figure 5 This is a SEM photo of the negative electrode zinc sheet of the Zn / Zn symmetrical battery obtained in Example 1 of the present invention after 50 cycles in 1M ZnSO4 electrolyte;

[0028] Figure 6 This is a SEM photo of the negative zinc sheet of the Zn / Zn symmetrical battery obtained in Example 1 of the present invention after 50 cycles in 1M ZnSO4 electrolyte and 0.05M SL;

[0029] Figure 7 This is a SEM photo of the negative zinc sheet of the Zn / Zn symmetrical battery obtained in Example 1 of the present invention after 50 cycles in 1M ZnSO4 electrolyte and 0.05M CL;

[0030] Figure 8 This is a SEM photo of the negative electrode zinc sheet of the Zn / Zn symmetrical battery obtained in Example 1 of the present invention after 50 cycles in 1M ZnSO4 electrolyte and 0.05MAL;

[0031] Fig. 9 The Zn / Cu half-cell assembled with sodium lignin sulfonate of different concentrations (0, 0.01M, 0.05M, 0.1M) obtained in Example 1 of the present invention was operated at a current density of 0.5 mA cm -2 and an area capacity of 0.25 mAh cm -2 Below is the Coulomb efficiency picture.

[0032] Fig.10 The Zn / Cu half-cell assembled with calcium lignin sulfonate of different concentrations (0, 0.01M, 0.05M, 0.1M) obtained in Example 1 of the present invention was subjected to a current density of 0.5 mA cm -2 and an area capacity of 0.25 mAh cm -2 Below is the Coulomb efficiency picture.

[0033] Fig.11The Zn / Cu half-cell assembled with different concentrations (0, 0.01M, 0.05M, 0.1M) of ammonium lignin sulfonate obtained in Example 1 of the present invention was operated at a current density of 0.5 mA cm -2 and an area capacity of 0.25 mAh cm -2 Below is the Coulomb efficiency picture.

[0034] Fig.12 This is a SEM photo of the Cu sheet of the Zn / Cu half-cell obtained in Example 1 of the present invention after 50 cycles in a 1M ZnSO4 electrolyte;

[0035] Fig.13 This is a SEM photo of the Cu sheet of the Zn / Cu half-cell obtained in Example 1 of the present invention after 50 cycles in 1M ZnSO4 and 0.05M SL electrolyte;

[0036] Fig.14 This is a SEM photo of the Cu sheet of the Zn / Cu half-cell obtained in Example 1 of the present invention after 50 cycles in 1M ZnSO4 and 0.05M CL electrolyte;

[0037] Fig.15 This is a SEM photo of the Cu sheet of the Zn / Cu half-cell obtained in Example 1 of the present invention after 50 cycles in 1M ZnSO4 and 0.05MAL electrolyte;

[0038] Fig.16 This is an XRD picture of the zinc-plated layer on the Cu sheet obtained in Example 1 of the present invention. The electroplating solutions are 1M ZnSO4 electrolyte containing 0.05M sodium lignin sulfonate, calcium lignin sulfonate and ammonium lignin sulfonate respectively.

[0039] Fig.17 This is the LSV curve obtained in Example 1 of the present invention, and the electrolyte is 1M ZnSO4 electrolyte containing 0.05M sodium lignin sulfonate, calcium lignin sulfonate and ammonium lignin sulfonate respectively.

[0040] Fig.18 This is a SEM photo of the PANI cathode in the Zn / / PANI full cell obtained in Example 1 of the present invention;

[0041] Fig.19 The Zn / / PANI full battery assembled with sodium lignin sulfonate of different concentrations (0, 0.002M) obtained in Example 1 of the present invention was used in 0.5Ag -1 Long cycle images at different current densities.

[0042] Fig. 20 This is a SEM photo of the MnO2 cathode in the Zn / / MnO2 full cell obtained in Example 1 of the present invention;

[0043] Fig.21The Zn / / MnO2 full battery assembled with different concentrations (0, 0.002M) of sodium lignin sulfonate obtained in Example 1 of the present invention was used in 5Ag -1 Long cycle images at different current densities. DETAILED DESCRIPTION

[0044] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiment.

[0045] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0046] Unless otherwise specified, the reagents and materials used in the following examples can be obtained from commercial sources.

[0047] The battery performance tests in the following examples were all conducted using the Xinwei battery test system. The negative electrode composite material obtained in the following examples, Ketjen black and PVDF were mixed and uniformly dissolved in NMP solution in a mass ratio of 70:20:10 to form a slurry, which was then uniformly coated on a titanium foil current collector to form a working electrode. The glass fiber membrane was used as a separator, and the electrolyte was a 1M ZnSO4 solution with / without sodium lignin sulfonate. The button cells were assembled in the air, and the test voltage range was 1.0V-1.8Vvs Zn / Zn 2+ .

[0048] Embodiment 1:

[0049] Step 1: Weigh 2.876 g of zinc sulfate heptahydrate (ZnSO4·7H2O) and 0.27 g of sodium lignin sulfonate powder and dissolve them in deionized water to prepare 10 ml of mixed liquid, and stir with a magnetic stirrer to accelerate the dissolution;

[0050] Step 2: The solution obtained by sufficient stirring is filtered by suction through a microporous filter membrane to remove insoluble impurities, thereby obtaining a 1M ZnSO4 electrolyte containing a 0.05M sodium lignin sulfonate additive.

[0051] Step 3: Weigh 2.876 g of zinc sulfate hexahydrate (ZnSO4·7H2O) and 0.26 g of calcium lignin sulfonate powder and dissolve them in deionized water to prepare 5 ml of mixed liquid, and stir with a magnetic stirrer to accelerate the dissolution;

[0052] Step 4: The solution obtained by sufficient stirring is filtered by suction through a microporous filter membrane to remove insoluble impurities, thereby obtaining a 1M ZnSO4 electrolyte containing a 0.05M calcium lignin sulfonate additive.

[0053] Step 5: Weigh 2.876 g of zinc sulfate hexahydrate (ZnSO4·7H2O) and 0.26 g of ammonium lignin sulfonate powder and dissolve them in deionized water to prepare 5 ml of mixed liquid, and stir with a magnetic stirrer to accelerate the dissolution;

[0054] Step 6: The solution obtained by sufficient stirring is filtered by suction through a microporous filter membrane to remove insoluble impurities, thereby obtaining a 1M ZnSO4 electrolyte containing a 0.05M ammonium lignin sulfonate additive.

[0055] Step 7: The electrolyte obtained in steps 2, 4, and 6 is used to assemble Zn / Zn symmetrical cells, Zn / Cu half cells, Zn / / MnO2, and Zn / / PANI full cells.

[0056] Step 8: Testing Zn / Zn symmetric cells containing lignin sulfonate at different current densities of 5 mA cm -2 and an area capacity of 0.5 mAh cm -2 The surface morphology of the Zn sheet, XRD and the number of cycles of the symmetric battery are shown below to prove that the sodium lignin sulfonate additive can guide the uniform deposition of zinc ions on the surface of the negative electrode zinc sheet.

[0057] Step 9: Assemble Zn / Cu half-cells with / without sodium lignin sulfonate and test at different current densities 0.5 mA cm -2 and an area capacity of 0.25 mAh cm -2 The surface morphology of the Cu sheet and the Coulombic efficiency of the half-cell were compared to explore the effect of lignin sulfonate on the morphology of zinc ion deposition.

[0058] Step 10: In the electrolytic cell, copper foil is used as the working electrode, zinc sheet is used as the counter electrode, sodium lignin sulfonate, calcium lignin sulfonate and ammonium lignin sulfonate are used as electrolyte additives and zinc sulfate is used to prepare the electrolyte, a zinc layer is plated on the copper sheet, and the mechanism of lignin sulfonate guiding the uniform deposition of zinc is obtained through XRD measurement.

[0059] Step 11: In the electrolytic cell, copper foil was used as the working electrode, zinc sheet was used as the counter electrode, sodium lignin sulfonate, calcium lignin sulfonate and ammonium lignin sulfonate were used as electrolyte additives and zinc sulfate was used to prepare the electrolyte, and Ag / AgCl electrode was used as the reference electrode. The hydrogen evolution potential of different electrolytes was tested using the LSV method in the Princeton electrochemical workstation.

[0060] Step 12: Assemble full cells with / without sodium lignin sulfonate additive electrolyte (Zn / / MnO2, Zn / / PANI) to determine the charge-discharge curves and long-cycle stability;

[0061] Figure 1The Zn / Zn symmetric battery assembled with different concentrations (0, 0.01M, 0.05M, 0.1M) of sodium lignin sulfonate obtained in Example 1 was charged at a current density of 5 mA cm -2 and an area capacity of 0.5 mAh cm -2 The long cycle diagram is shown below. It can be clearly seen from the figure that the battery assembled by 1M ZnSO4 electrolysis short-circuited after 65h of cycling. After adding 0.05M SL, the symmetric Zn / Zn battery can be stably cycled for more than 6500h. It can be seen that SL has a positive effect on the stable deposition of zinc ions.

[0062] Figure 2 The Zn / Zn symmetric battery assembled with different concentrations (0, 0.01M, 0.05M, 0.1M) of calcium lignin sulfonate obtained in Example 1 was charged at a current density of 5 mA cm -2 and an area capacity of 0.5 mAh cm -2 The long cycle diagram is shown below. It can be clearly seen from the figure that the battery assembled by 1M ZnSO4 electrolysis short-circuited after 45h of cycling. After adding 0.05M CL, the symmetric Zn / Zn battery can be stably cycled for more than 1000h. It can be seen that CL has a positive effect on the stable deposition of zinc ions.

[0063] Figure 3 The Zn / Zn symmetric battery assembled with different concentrations (0, 0.01M, 0.05M, 0.1M) of ammonium lignin sulfonate obtained in Example 1 was operated at a current density of 5 mA cm -2 and an area capacity of 0.5 mAh cm -2 The long cycle diagram is shown below. It can be clearly seen from the figure that the battery assembled by 1M ZnSO4 electrolysis short-circuited after 75h of cycling. After adding 0.05MAL, the symmetric Zn / Zn battery can be stably cycled for more than 800h. It can be seen that AL has a positive effect on the stable deposition of zinc ions.

[0064] Figure 4 XRD photos of the negative zinc sheet of the Zn / Zn symmetric battery assembled with sodium lignin sulfonate, calcium lignin sulfonate and ammonium lignin sulfonate of the same concentration (0.05M) obtained in Example 1 of the present invention after 50 cycles. It can be clearly seen from the figure that the peak of the by-product Zn4SO4(OH)6·xH2O can be clearly found in the battery assembled by 1M ZnSO4 electrolysis. After adding 0.05MSL, AL and CL, the peak intensity of the by-product is significantly weakened, proving that lignin sulfonate can effectively inhibit the generation of by-products.

[0065] Figure 5This is a SEM photo of the negative zinc sheet of the Zn / Zn symmetrical battery obtained in Example 1 of the present invention after 50 cycles in 1M ZnSO4 electrolyte. It can be clearly seen that the surface of the zinc sheet is covered with a layer of polygonal byproducts.

[0066] Figure 6 This is a SEM photo of the negative zinc sheet of the Zn / Zn symmetrical battery obtained in Example 1 of the present invention after 50 cycles in 1M ZnSO4 and 0.05M SL electrolyte. It can be clearly seen that there is a uniform coating on the surface of the zinc sheet, proving that SL can uniformly guide zinc deposition.

[0067] Figure 7 This is a SEM photo of the negative zinc sheet of the Zn / Zn symmetrical battery obtained in Example 1 of the present invention after 50 cycles in 1M ZnSO4 and 0.05M SL electrolyte. It can be clearly seen that the zinc sheet surface coating is uniform and no by-products are generated, proving that CL can uniformly guide zinc deposition.

[0068] Figure 8 This is a SEM photo of the negative zinc sheet of the Zn / Zn symmetrical battery obtained in Example 1 of the present invention after 50 cycles in 1M ZnSO4 and 0.05M SL electrolyte. It can be clearly seen that the zinc sheet surface coating is uniform and no by-products are generated, proving that AL can uniformly guide zinc deposition.

[0069] Fig. 9 The Zn / Cu half-cell obtained in Example 1 of the present invention is -2 and an area capacity of 0.25 mAh cm -2 The following is a picture of coulombic efficiency. It can be clearly seen that the battery assembled by 1M ZnSO4 electrolysis short-circuited after 6 hours of cycling. After adding 0.05M SL, the symmetric Zn / Zn battery can stably cycle for more than 1000 hours and the coulombic efficiency is maintained at 99.6%. It can be seen that SL can stably deposit zinc ions on the surface of the Cu substrate.

[0070] Fig.10 The Zn / Cu half-cell obtained in Example 1 of the present invention is -2 and an area capacity of 0.25 mAh cm -2 The following is a picture of coulombic efficiency. It can be clearly seen that the battery assembled by 1M ZnSO4 electrolysis short-circuited after 6 hours of cycling. After adding 0.05M SL, the symmetric Zn / Zn battery can stably cycle for more than 800 hours and the coulombic efficiency is maintained at 99.6%. It can be seen that SL can stably deposit zinc ions on the surface of the Cu substrate.

[0071] Fig.11The Zn / Cu half-cell obtained in Example 1 of the present invention is -2 and an area capacity of 0.25 mAh cm -2 The following is a picture of coulombic efficiency. It can be clearly seen that the battery assembled by 1M ZnSO4 electrolysis short-circuited after 6 hours of cycling. After adding 0.05M SL, the symmetric Zn / Zn battery can stably cycle for more than 650 hours and the coulombic efficiency is maintained at 99.6%. It can be seen that SL can stably deposit zinc ions on the surface of the Cu substrate.

[0072] Fig.12 This is a SEM photograph of the Cu sheet after the Zn / Cu half-cell obtained in Example 1 of the present invention has been cycled 50 times in a 1M ZnSO4 electrolyte; it can be clearly seen that the surface of the Cu sheet is covered with a layer of polygonal byproducts.

[0073] Fig.13 This is a SEM photo of the Cu sheet after the Zn / Cu half-cell obtained in Example 1 of the present invention was cycled for 50 cycles in 1M ZnSO4 and 0.05M SL electrolyte. It can be clearly seen that there is a uniform filamentary coating on the surface of the zinc sheet, proving that SL can participate in guiding the uniform deposition of zinc ions on the Cu sheet and inhibit the generation of by-products.

[0074] Fig.14 This is a SEM photo of the Cu sheet after the Zn / Cu half-cell obtained in Example 1 of the present invention was cycled for 50 cycles in 1M ZnSO4 and 0.05M CL electrolyte. It can be clearly seen that there is a uniform filamentary coating on the surface of the zinc sheet, proving that CL can participate in guiding the uniform deposition of zinc ions on the Cu sheet and inhibit the generation of by-products.

[0075] Fig.15 This is a SEM photo of the Cu sheet after the Zn / Cu half-cell obtained in Example 1 of the present invention was cycled for 50 cycles in 1M ZnSO4 and 0.05MAL electrolyte. It can be clearly seen that there is a uniform filamentary coating on the surface of the zinc sheet, proving that AL can participate in guiding the uniform deposition of zinc ions on the Cu sheet and inhibit the generation of by-products.

[0076] Fig.16 The XRD image of the zinc-plated layer on the Cu sheet obtained in Example 1 of the present invention is shown in Figure 1. The electroplating solution is a 1M ZnSO4 electrolyte containing 0.05M sodium lignin sulfonate, calcium lignin sulfonate and ammonium lignin sulfonate. It can be clearly seen that for the 1M ZnSO4 electrolyte, the ratio of the Zn (002) crystal plane to the Zn (100) crystal plane is 1.0. After adding lignin sulfonate, the ratio can be increased to more than 1.67. It is proved that lignin sulfonate can effectively guide zinc ions to deposit on the regular (002) crystal plane, thereby obtaining a uniform zinc coating.

[0077] Fig.17 This is the LSV curve obtained in Example 1 of the present invention, and the electrolyte is a 1M ZnSO4 electrolyte containing 0.05M sodium lignin sulfonate, calcium lignin sulfonate and ammonium lignin sulfonate. It can be clearly seen that the hydrogen evolution potential of the electrolyte with lignin sulfonate added is significantly higher than that of the 1M ZnSO4 electrolyte, proving that lignin sulfonate can effectively inhibit the occurrence of hydrogen evolution side reaction in aqueous electrolyte.

[0078] Fig.18 This is a SEM photo of the PANI cathode in the Zn / / PANI full cell obtained in Example 1 of the present invention. PANI is prepared by chemical in-situ polymerization on carbon felt. It can be clearly seen that the carbon fibers are covered with nano-scale PANI sheets.

[0079] Fig.19 The Zn / / PANI full battery obtained in Example 1 of the present invention is 0.5Ag -1 Long cycle picture under current density. It can be clearly seen that the full battery containing SL has a higher charge and discharge capacity and the capacity does not decay after 1000 cycles.

[0080] Fig. 20 This is a SEM photo of the MnO2 cathode in the Zn / / MnO2 full cell obtained in Example 1 of the present invention. MnO2 is prepared by a chemical one-pot method. It can be clearly seen that MnO2 shows a nanosheet morphology.

[0081] Fig.21 The Zn / / MnO2 full battery obtained in Example 1 of the present invention is 5Ag -1 Long cycle pictures under current density. It can be clearly seen that the full battery containing SL exhibits higher reversible capacity and better cycle stability.

[0082] In summary, the aqueous zinc ion battery electrolyte containing lignin sulfonate (sodium lignin sulfonate, calcium lignin sulfonate, ammonium lignin sulfonate) additive prepared by the present invention has excellent performance.

Claims

1. An aqueous zinc ion battery electrolyte using wheat straw extract as a biomass organic salt additive, characterized in that: Constructing an aqueous zinc ion battery using the aqueous zinc ion battery electrolyte; The aqueous zinc ion battery electrolyte comprises zinc sulfate, deionized water and a biomass organic salt additive; the biomass organic salt additive is a straw extract selected from sodium lignin sulfonate, calcium lignin sulfonate or ammonium lignin sulfonate; The concentration of zinc sulfate in the aqueous zinc ion battery electrolyte is 1M; The concentration of the biomass organic salt additive in the aqueous zinc ion battery electrolyte is 0.05M; The aqueous zinc ion battery electrolyte is prepared by the following steps: Step 1: Weigh zinc sulfate hexahydrate and biomass organic salt additive powder and dissolve them in deionized water, prepare 3-7 ml of the mixed liquid, and stir with a magnetic stirrer to accelerate the dissolution and uniform dispersion; Step 2: The solution obtained in step 1 is filtered by suction through a microporous filter membrane to remove insoluble impurities.

2. The aqueous zinc ion battery electrolyte according to claim 1, wherein: The aqueous zinc ion battery includes a Zn / Zn symmetric cell, a Zn / Cu half cell, a Zn / / MnO2 or a Zn / / PANI full cell.